Does it help to be rich? an assessment of the differences between developing and developed countries and the correlation between investment in healthcare and country performance during the COVID-19 pandemic - Octaviano, Maurice Kyla T.; Panaguiton, Miranda Bernadette A.
The SARS-CoV-2 virus has spread throughout the world, resulting in the COVID-19 pandemic that has infected many individuals across various countries. This study aims to assess the differences between developed and developing countries as well as the correlation between investment in healthcare and a country’s performance during the pandemic. Performance during the COVID-19 pandemic is measured by how effectively a country is able to mitigate the spread of the virus, which is observed through its average total cases per thousand individuals. Lockdown response, rate of testing, contract tracing, and a country’s healthcare system capacity are all considered crucial healthcare investments that are used to curb transmissions of the virus. On the other hand, other factors unrelated to investments in healthcare such as political, cultural, and religious nuances may also affect increases or decreases in the number of cases. From this study, the researchers concluded the following: (1) developed countries are more likely to have a higher number of average total cases per thousand; (2) rate of testing and contact tracing are the most important factors that are significantly correlated with a country’s average total cases per thousand; (3) lockdown responses and a country’s number of hospital beds are insignificantly correlated with average total cases per thousand; and (4) political, cultural, and religious nuances may play a large role when it comes to increases and decreases in the average total cases per thousand.